Los materiales didácticos y su influencia en el desarrollo motriz de los niños y niñas de 4 años, del centro educativo Prisca Linder de la parroquia San Antonio de Pichincha de la ciudad de Quito, período lectivo 2012 – 2013 - Betancourt Diaz, Laura Rosario (2013)
The present research work is called : THE TEACHING MATERIALS AND THEIR INFLUENCE ON PLANT DEVELOPMENT CHILDREN OF 4 YEARS , THE EDUCATION CENTER " PRISCA LINDER " SAN ANTONIO DE PICHINCHA PARISH LOCATED IN QUITO CITY , TERM PERIOD 2012 - 2013 , the same that was structured according to current regulation Graduation National University of Loja. Its overall goal: Raise awareness among teachers, authorities and parents about the importance of the Instructional Materials Motor Development for children aged four years, the School "Prisca Linder" Parish San Antonio de Pichincha City of Quito, school period 2012-2013. Methods and techniques for data collection and data analysis were: The Scientific Method, Inductive - Deductive, Analytical - Synthetic, Descriptive, and Statistical Model, the same that were used to identify, describe, interpret and analyze the issues raised. The techniques and instruments comprise: The survey of teachers for the use of the teaching materials in their daily work, for the Motor Development; and, the test of Motor Proficiency Ozeretski to assess the Motor Development of Children Education Center "Prisca Linder" in San Antonio de Pichincha parish located in Quito. With the implementation of the survey found that 100 % of the teachers expressed using in the daily work, Representational and Graphic Material (games and puzzles) and Structured Concrete Material (blocks, threading figures) for the Motor Development. With the application of the test of Motor Proficiency Ozeretski to assess the Motor, 51% of children obtained a rating scale of Unsatisfactory, and 49 % achieved a rating of Satisfactory.